Evaluation of bone mineral density and body compositions interrelation in young and middle-aged male patients with Crohn’s disease by quantitative computed tomography - Zhang, Xueli; Peng, Kun; Li, Gang; Wan, Lidi; Xu, Tingting; Cui, Zhijun; Xiao, Fuxia; Li, Li; Liu, Zhanju; Zhang, Lin; Tang, Guangyu (Frontiers in Endocrinology, 2022)
Background The aim of this study was to investigate the characteristics of bone mineral density (BMD) and body compositions, and the impact of body compositions on BMD in young and middle-aged male patients with Crohn’s disease (CD). Methods Patients with CD (n = 198) and normal controls (n = 123) underwent quantitative computed tomography (QCT) examination of lumbar vertebrae 1–3 (L1–3). The BMD and bone geometric parameters were measured and outputted by QCT post-process software. Meanwhile, body composition parameters, including subcutaneous adipose tissue (SAT), visceral adipose tissue (VAT), lean mass (LM), and muscles mass around lumbar vertebrae were also acquired by QCT. Blood indicators [interleukin (IL)-6, IL-8, tumor necrosis factor alpha (TNF-α), C-reactive protein (CRP), Ca, and P] were collected from clinical medical records. Independent t-test was used to compare these variables between the CD group and the normal control group. Results There was no significant difference in age, height, and weight between the CD group and the control group (p > 0.05), indicating that the sample size was relatively balanced. Mean BMD in the CD group were lower than those in the control group, but the difference was not statistically significant (p > 0.05). The bone geometric parameters of the CD group, including cortical area/density (Ct. Ar, Ct. BMD) and trabecular area/density (Tb. Ar and Tb. BMD), were significantly lower than those of the control group (p < 0.05), so were the body composition parameters including total adipose tissue (TAT), visceral adipose tissue (VAT), subcutaneous adipose tissue (SAT), lean mass (LM), and muscles mass (p < 0.05). In addition, the level of plasma IL-6, IL-8, CRP, and TNF-α of the CD group were higher than those of the control group (p < 0.05). On the contrary, the body mass index (BMI) and serum Ca and P levels of the CD group were lower than those of the control group (p < 0.05). Through multiple linear regression analysis, Tb. BMD, VAT, Ct. Ar, LM, Ca, and IL-8 entered the regression model and revealed a significant contribution to BMD. Conclusions Patients with CD could suffer from reduction in BMD. However, the parameters of bone geometric parameters are more sensitive and accurate than BMD changes. Among them, Tb. BMD, VAT, Ct. Ar, and LM have significant effects on BMD reduction.